2023
DOI: 10.3389/fcvm.2023.1154708
|View full text |Cite
|
Sign up to set email alerts
|

A modern day perspective on smoking in peripheral artery disease

Abstract: Peripheral artery disease (PAD) is associated with increased risk of cardiovascular morbidity and mortality, poor functional status, and lower quality of life. Cigarette smoking is a major preventable risk factor for PAD and is strongly associated with a higher risk of disease progression, worse post-procedural outcomes, and increased healthcare utilization. The arterial narrowing due to atherosclerotic lesions in PAD leads to decreased perfusion to the limbs and can ultimately cause arterial obstruction and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Analyzing risk factors explaining the effect of genetic liability to MDD on CVDs, we observed that only the association between genetic liability to MDD and coronary artery disease remained statistically significant after adjusting for psychosocial/lifestyle or metabolic covariates in a multivariable MR analysis. In addition, we found that smoking status attenuates the association between genetic liability to MDD and peripheral artery disease, for which smoking is a particularly strong risk factor 55 . Interestingly, we find that loneliness is an equally important factor explaining the relationship between MDD and peripheral artery disease, as well as heart failure, which is in line with the results from the adjusted genome-wide genetic correlation analysis discussed above.…”
Section: Discussionmentioning
confidence: 72%
“…Analyzing risk factors explaining the effect of genetic liability to MDD on CVDs, we observed that only the association between genetic liability to MDD and coronary artery disease remained statistically significant after adjusting for psychosocial/lifestyle or metabolic covariates in a multivariable MR analysis. In addition, we found that smoking status attenuates the association between genetic liability to MDD and peripheral artery disease, for which smoking is a particularly strong risk factor 55 . Interestingly, we find that loneliness is an equally important factor explaining the relationship between MDD and peripheral artery disease, as well as heart failure, which is in line with the results from the adjusted genome-wide genetic correlation analysis discussed above.…”
Section: Discussionmentioning
confidence: 72%
“…On multivariable MR analysis, we observed that only the association between genetic liability to MDD and coronary artery disease remained statistically significant after adjusting for the psychosocial or lifestyle or metabolic covariates. We found that adjusting for smoking status attenuates the association between genetic liability to MDD and peripheral artery disease, for which smoking is a strong risk factor 67 . Interestingly, we find that loneliness is an equally important factor explaining the relationship between MDD and peripheral artery disease.…”
Section: Discussionmentioning
confidence: 75%
“…Studies on IAC, report positive associations with smoking and dyslipidemia ( 35 , 50 ). Nicotine found in tobacco promotes vascular calcification, and its mechanisms involve the hyperactivation of inflammatory responses, oxidative stress, autophagy, increased cell apoptosis, extracellular matrix degradation, and disruption of endothelial function ( 51 53 ). LDL causes the formation of atherosclerosis through various mechanisms, including the upregulation of inflammatory cytokines and adhesion molecules on vascular endothelial cells, increased transport of oxPLs, inhibition of nitric oxide synthesis, resulting in vascular remodeling, and promotion of smooth muscle cell proliferation and foam cell formation ( 54 ).…”
Section: Clinical Relevance Of Llacmentioning
confidence: 99%